Tindak Tutur Ilokusi A Pragmatic Analysis of Illocutionary Speech Acts in the Drama Lutung Kasarung by EKI Dance Company as an Alternative Teaching Module for the Merdeka Curriculum - Maharani Puspa Dewi; Stella Talitha; Ruyatul Hilal Mukhtar (The Future of Education Journal, 2026)
Drama, as both a literary work and a medium of communication, contains various forms of language use that represent social interactions among characters. One of the important pragmatic aspects to be examined in drama is illocutionary speech acts, as utterances serve not only to convey information but also to express specific intentions and purposes. This study aims to describe the forms of illocutionary speech acts in the drama Lutung Kasarung by EKI Dance Company and to explore their implications for Indonesian language teaching at the senior high school level. The study adopts John R. Searle’s theory of illocutionary speech acts, which classifies illocutionary acts into five categories: assertives, directives, commissives, expressives, and declarations. A descriptive qualitative method was employed, with the dialogues among the characters in Lutung Kasarung serving as the data source. Data were collected through documentation using observation and note-taking techniques, while data credibility was established through triangulation involving two lecturers in Indonesian Language and Literature Education and one senior high school Indonesian language teacher. The findings identified 62 instances of illocutionary speech acts, consisting of 20 directive acts, 20 assertive acts, 3 commissive acts, 15 expressive acts, and 4 declarative acts. Directive and assertive speech acts were found to be the most dominant types used in the dramatic dialogues. These findings have implications for Indonesian language instruction at the senior high school level, particularly in the development of teaching modules aligned with the Merdeka Curriculum, with a focus on listening, reading, and viewing drama texts. Therefore, Lutung Kasarung can serve as an alternative instructional resource for enhancing students' pragmatic competence, critical thinking skills, and literary appreciation.